Rosmarinus officinalis L. e Triticum aestivum no tratamento da otite externa infecciosa - Fontoura, Eduardo Garcia (2014)
External otitis is an inflammation of the outer ear and ear canal, which may or may not be of infectious cause. Negligence will lead to recurrence, hampering treatment and causing bacterial resistance to conventional methodologies. In this context, medicinal plants and plant extracts may be an alternative. Triticum aestivum (wheat) has been shown to act as an antioxidant, anti-inflammatory, pain-killer, as well as used in wound healing. Rosmarinus officinalis L. (rosemary) has antibacterial, anti-inflammatory, pain-killer, anti-mutagenic, diuretic, expectorant, and antioxidant effects. In this context, the objective of this study was to assess the use of wheat and rosemary aqueous extracts, and rosemary essential oil, in the treatment of infectious external otitis. Experimental otitis was induced in rats Wistar with croton oil at 5% in acetone, followed by the introduction of Staphylococcus aureus in the outer ear canal. Animals were separated according to the treatment group: GI 25% wheat aqueous extract in propylene glycol; GII 25% rosemary aqueous extract in propylene glycol; GIII 5% rosemary essential oil in propylene glycol; GIV propylene glycol; and GV saline. The animals were treated for up to seven days, and assessed regarding clinical (according to the Emgard & Hellström method) and hitopathological alterations, on days four, six and ten. Promising results were observed on animals treated with both aqueous extracts, primarily in GI (wheat), but also in GII (rosemary), both were able to reduce clinical and histopathological parameters beyond the effect of the control. This study shows that the aqueous extract of both T. aestivum and R. oficinallis promoted the hastening of the healing process of infectious external otitis.